Doubling farmers’ income through technological innovations - Mysore, Sudha (Indian Horticulture, 2019)
There are a number of successful cases, wherein adoption of improved varieties and hybrids released by IIHR, Bengaluru, have led to definite enhancement not only to the crop productivity, but also to the farm family income. Keeping these facts in view, this article attempts to bring forth the role and prospects of horticultural crop based technologies towards the objective of doubling farmers’ income.